Successful En-Bloc Kidney Transplantation from a 5-Month-Old Donor to a 63-Year Old Recipient: A case report. (August 2017) - Kang, Seong Sik; Park, Ha Yeon; Yeo, Sang Mok; Park, Woo Yeong; Han, Seungyeup; Park, Sung Bae; Park, Ui Jun; Kim, Hyoung Tae; Yoon, Jeongsoo; Jin, Kyubok
Abstract : Introduction: Pediatric deceased donor kidney transplantation (DDKT) has been increasing gradually as a donor pool expansion method. In addition, the outcomes of pediatric DDKT over the last 20 years have shown excellent results with an active practice of en-bloc KT (EBKT) which increases kidney volume. We report pediatric en-bloc KT performed with organ donation from the youngest 5-month-old infant in our institution. Presentation of Case: En-block kidney of a 5-month-old female infant with a body weight of 3.2 kg diagnosed with brain death due to hypoxic injury was transplanted into a 63-year old female patient with a body weight of 56 kg, who was receiving continuous ambulatory peritoneal dialysis (CAPD) for IgA nephropathy end-stage renal disease. The human leukocyte antigen mismatches were 3 and both panel reactive antibody and donor-specific antibody were negative. Basiliximab was used as the induction immunosuppressant. Results: Cold ischemia times were 187 minutes. Both kidneys weighed 56 g and distal ends of the donor aorta and vena cava were anastomosed to internal iliac artery and external iliac vein of the recipient. Tacrolimus, mycophenolate mofetil, and prednisolone were used as the maintenance immunosuppressant. Postoperative renal doppler sonography showed mild hydronephrosis in one kidney and small amount perinephric free fluid collection, but both improved in follow-up examination. On the 20th day of KT, the serum creatinine level decreased to 1.23 mg/dL with estimated glomerular filtration (eGFR) 44.1 mL/min/1.73 m 2 and CAPD catheter was removed. At 5 months after KT, serum creatinine was 0.90 mg/dL and eGFR was 63.0 mL/min/1.73 m 2 . Conclusion: This case report highlights the successful KT to an adult with en-bloc kidney of a 5-month-old infant. And long-term follow-up on whether small kidneys of 56 g adapt appropriately and function well in adult is needed.